Nursing in Epidemiology: A Specialized Role and its Impact on Public Health and Health Systems - Alcalá-Albert , Gregorio Jesús; Becerra , Gloria Marlen Aldana-De; López-Alcalá , Jaime; Parra-González , María Elena (Journal of Ecohumanism, 2025)
Nursing and Epidemiology share the common purpose of their concern for human health. The aim was to analyse the scientific production of Nursing in Epidemiology from 1958 to 2023 in the WoS database, obtaining a total of 1032 articles. The results show a thematic adaptation to the different stages of Epidemiology with a growth throughout history and increasing significantly since 2019, production that has been maintained in subsequent years due to the COVID-19 pandemic. Most of the authors are affiliated to US universities, being the first country in scientific production, followed by China with a growing trend in cooperation between the two. Nursing demonstrates its capacity to carry out epidemiological research, overcoming the usual conception of being a health care profession and contributing a leading role in management and leadership, as well as in research. The relevance of nursing and its scientific contributions in the field of public health and epidemiology in an increasingly globalised world must be recognised.